Polemik Penulisan Hadis: Perspektif Michael A. Cook dalam The Opponents of the Writing of Tradition in Early Islam - Farida, Umma (RIWAYAH, 2015)
AbstractCook’s work entitled The Opponents  of the Writing  of Tradition in Early Islam focuses more on opposition to writing traditions (hadith) that occurred in the early days of Islam in the process of shifting the oral tradition in Hadith narration into a written tradition, and did not expose the chronology for writing  tradition itself. Cook classified the opposition in writing hadith in the early days of Islam into two phases, namely Basra phase and common phase which includes Kufa, Medina, Mecca, Yemen, and Syria, and their arguments which are built by each phase, as well as patterns of compromise adopted to connect the two opposite opinions